MEMBANGUN SIKAP TOLERAN DAN DEMOKRATIS MELALUI PENDIDIKAN AGAMA ISLAM - Gafur, Abdul; Mutholingah, Siti; Munir, Misbahul (TA'LIMUNA: Jurnal Pendidikan Islam, 2021)
The condition of Indonesian society which is plural and multiculture can trigger socio-religious conflicts. These conflicts can be reduced or even avoided if the Indonesian people always apply the values of tolerance and democracy in their daily life. In this case, Islamic education as a process and part of the national education system certainly has a very important role in the context of growing and developing a tolerant and democratic attitude for students. The implementation of Islamic Education should lead to the internalization of the values of tolerance and democracy which include the values of justice, freedom, responsibility, equality, deliberation, pluralism so that students become good individuals in their families, communities, countries and their environment.